Development of Cutaneous Bioadhesive Ureasil-Polyether Hybrid Films - João Augusto Oshiro Junior; Flávia Chiva Carvalho; Christiane Pienna Soares; Marlus Chorilli; Leila Aparecida Chiavacci (International Journal of Polymer Science)
The hydrolysis and condensation reactions involved in synthesis of ureasil-polyether films influence the film formation time and the number of chemical groups able to form hydrogen bonds, responsible for the bioadhesion, with the biological substrate. The objective of this work was to study the influence of the use of an acid catalyst (hydrochloric acid) and a basic catalyst (ammonium fluoride) in the hydrolysis and condensation reactions on the time formation and bioadhesion of ureasil-polyether films. The toxicity of the films was evaluated. The MTT assay has shown cell viability of human skin keratinocytes higher than 70% of all analyzed materials suggesting low cytotoxicity. The bioadhesion of the films is strongly dependent on the viscosity and hydrophilic/hydrophobic balance of the polyether chains used to synthetize the hybrid molecules. The use of acid catalyst promotes the formation of less viscous films with higher bioadhesion. The hybrids formed by more hydrophilic PEO chains are more bioadherent, since they can interact more efficiently with the water present in the stratum corneum increasing the bioadhesion. Due to their low toxicity and high bioadhesion, the ureasil-PEO films obtained by using HCl as catalyst agent are good candidates for application to the skin as bioadhesive films.